Monetary policy and learning in an open economy - Martin Ellison; Lucio Sarno; Jouko Vilmunen (Bank of Finland, 2004)
In this paper, we examine the incentives for central bank activism and caution in a two-country open-economy model with uncertainty and learning.We find that the presence of a strategic interaction between the home and foreign central banks creates an additional motivation for caution in monetary policy.An activist policy designed to help the learning of the home central bank is suboptimal since it generates a strong reaction from the foreign central bank.As joint learning by the home and foreign central banks is shown to be detrimental to welfare, the optimal policy is cautious.
URN:NBN:fi:bof-20140807466
Keywords: D81; D83; E52; E58; F41; 330; activism; learning; monetary policy; open economy